Generating value across academic and professional design practice in the Internet of Things. Issue 1 (2nd January 2019) - Robbins, Holly; Giaccardi, Elisa
ABSTRACT: This article accounts for how value in design research can be derived from knowledge exchange that occurs through the collaborative discourse of doing design. To demonstrate this point, the article details the arc and impact of a design research collaboration that extended over several years with design practitioners in the field of internet-connected devices. As a result of this ongoing collaborative work, a programmatic set of design ideals and intentions concerning how to construct a more transparent and ethical relationship with technology was shaped. We examine this sustained and transformative collaboration as a series of knowledge exchanges. Within each particular collaborative project, worldviews and knowledge are exchanged among design researchers and practitioners, enabling them to traverse 'through practices' of academic and professional design. To unpack these exchanges and how they built and fed into each other, the article examines how collaboration unfolded and produced value on two levels: first on the scale of the academics and practitioners directly involved in a project; and secondly on the scale of the larger international community of design practitioners concerned with Internet-connected devices, with whom we had shared our work.